The Aesthetic Self. The Importance of Aesthetic Taste in Music and Art for Our Perceived Identity - Fingerhut, Joerg; Gomez-Lavin, Javier; Winklmayr, Claudia; Prinz, Jesse J. (Frontiers in Psychology, 2021)
To what extent does aesthetic taste and our interest in the arts constitute who we are? We present a series of empirical findings of an Aesthetic Self Effect supporting the claim that our aesthetic engagements are regarded as a central component of our identity: we have aesthetic selves. Counterfactual changes in aesthetic preferences, for example, moving from liking classical music to liking pop, are perceived as altering us as a person. This Aesthetic Self Effect is as strong as the impact of moral changes, such as altering political partisanship or religious orientation, and significantly stronger than for other categories of taste, such as food preferences (Pretest/Study 1, n = 251/359). Using a multidimensional scaling technique to model perceived aesthetic similarities among musical genres, we determined that aesthetic distances between genres correlate highly with the perceived difference in identity (Pretest/Study 2, n = 45/364). Further studies generalize the Aesthetic Self Effect beyond the musical domain: general changes in visual art preferences, for example from more traditional to abstract art, also elicited a strong Self Effect (Study 3, n = 237). Exploring the breadth of this effect we found an additional Anaesthetic Self Effect. That is, hypothetical changes from aesthetic indifference to caring about music, art or beauty are judged to have a significant impact on identity. This effect is stronger for aesthetic fields compared to adopting leisure activities, such as hiking or playing video games (Study 4, n = 305). Indeed, across our studies the Anaesthetic Self Effect turns out to be even stronger than the Aesthetic Self Effect. Taken together we found evidence for a link between aesthetics and identity: when our taste in music and the arts or our aesthetic interests change, we take these changes to severely transform us.